2001
DOI: 10.1002/mus.1169
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged median sensory latency as a predictor of future carpal tunnel syndrome

Abstract: The purpose of the study was to determine whether abnormal median sensory nerve conduction among asymptomatic workers was predictive of future symptoms suggestive of carpal tunnel syndrome (CTS). This was a prospective study involving 77 workers who were identified as asymptomatic cases with electrodiagnostic findings of median mononeuropathy compared to an age- and sex-matched control group. Follow-up was completed an average of 70 months later, and subjects who reported pain, numbness, tingling, or burning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 9 publications
4
54
2
4
Order By: Relevance
“…Consistent findings have shown that asymptomatic individuals with median neuropathy have a 3-4 fold increased risk of developing CTS over a period of 5-10 years.13, 15,[34][35][36] Though the majority of people with asymptomatic median neuropathy will not develop symptoms,34 this finding may represent a preclinical stage of CTS in a subset of individuals. Other studies have shown that risk factors for median neuropathy are similar to those for symptomatic CTS.…”
Section: Limitationsmentioning
confidence: 88%
“…Consistent findings have shown that asymptomatic individuals with median neuropathy have a 3-4 fold increased risk of developing CTS over a period of 5-10 years.13, 15,[34][35][36] Though the majority of people with asymptomatic median neuropathy will not develop symptoms,34 this finding may represent a preclinical stage of CTS in a subset of individuals. Other studies have shown that risk factors for median neuropathy are similar to those for symptomatic CTS.…”
Section: Limitationsmentioning
confidence: 88%
“…The CTS case definition used in this study was very similar to the case definitions used in other epidemiologic studies of CTS [Stetson et al, 1993;Atroshi et al, 1999;Stevens et al, 2001;Werner et al, 2001].…”
Section: Cts Case Definitionmentioning
confidence: 92%
“…The peak latencies of the median and ulnar 8-cm palm-to-wrist mixed nerve action potentials were recorded. Median mononeuropathy was defined as a medianulnar latency difference of 0.5 ms or greater which is similar to the criterion used in other studies [Monga et al, 1985;Redmond and Rivner, 1988;Werner et al, 1998Werner et al, , 2001Sander et al, 1999;Stevens et al, 2001]. If a median mixed nerve latency was not obtained because of a conduction block in the carpal tunnel, an 8 cm median motor orthodromic latency greater than 4.4 ms was used as the criterion for median neuropathy.…”
Section: Cts Case Definitionmentioning
confidence: 98%
See 1 more Smart Citation
“…The most common form of involvement is bilateral and the severity of the symptoms is generally more prominent in the dominant hand. 3,4 The initial symptoms of CTS are paresthesias, hypoesthesia, and hypalgesia in the median nerve sensory dermatome. At later stages, numbness and pain can develop and may radiate up to the elbow and shoulder.…”
Section: Introductionmentioning
confidence: 99%